The Effect of Company Performance, Company Complexity, Company Size on the Board of Commissioners Structure Moderated by Managerial Ownership - Carlos Pangestu, Juan; Whittleliang Hakki, Tandry; Naftalia Elisa, Marta (Journal of Accounting and Finance Management, 2024)
The role of the Board of Commissioners is very important to minimize agency problems so that shareholder wealth maximization can be achieved. Under one board, a number of studies have investigated the effect of the effectiveness of the Board of Directors on their company's performance. In Indonesia, existing research related to the effectiveness of the Board of Commissioners investigates the effectiveness of the Board of Commissioners as one of the determining factors for the possibility of financial distress and investigates effectiveness. This study aims to examine the effect of Company Performance, Company Complexity, Company Size on the Structure of the Board of Commissioners and examine whether there is a role of Managerial Ownership as a moderation in the influence of Company Performance, Company Complexity, Company Size on the Structure of the Board of Commissioners carried out by the company. This study took the research population from financial sector companies listed on the Indonesia Stock Exchange for the period 2019-2022. The type of data used in this study is secondary data in the form of company financial reports that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of the study, it shows that company performance has a significant effect on the Board of Commissioners Structure, then Company Complexity and Company Size do not have a significant effect on the Board of Commissioners structure. Managerial Ownership strengthens the influence of Company Performance on the Board of Commissioners Structure. Managerial Ownership does not strengthen the influence of Company Complexity and Company Size on the Board of Commissioners Structure.